China and great power responsibility for climate change - Kopra, Sanna (Taylor & Francis, 2018)
As American leadership over climate change declines, China has begun to identify itself as a great power by formulating ambitious climate policies. Based on the premise that great powers have unique responsibilities, this book explores how China's rise to great power status transforms notions of great power responsibility in general and international climate politics in particular. The author looks empirically at the Chinese party-state's conceptions of state responsibility, discusses the influence of those notions on China's role in international climate politics, and considers both how China will act out its climate responsibility in the future and the broader implications of these actions. Alongside the argument that the international norm of climate responsibility is an emerging attribute of great power responsibility, Kopra develops a normative framework of great power responsibility to shed new light on the transformations China's rise will yield and the kind of great power China will prove to be. The book will be of interest to students and scholars of international relations, China studies, foreign policy studies, international organizations, international ethics and environmental politics.